Preventive skin analgesia with lidocaine patch for management of post‐thoracotomy pain: Results of a randomized, double blind, placebo controlled study - Alfonso Fiorelli; Caterina Pace; Roberto Cascone; Annalisa Carlucci; Emanuele De Ruberto; Anna Cecilia Izzo; Beatrice Passavanti; Paolo Chiodini; Vincenzo Pota; Caterina Aurilio; Mario Santini; Pasquale Sansone (Thoracic Cancer, 2019)
Background To evaluate whether pre‐emptive skin analgesia using a lidocaine patch 5% would improve the effects of systemic morphine analgesia for controlling acute post‐thoracotomy pain. Methods This was a double‐blind, placebo controlled, prospective study. Patients were randomly assigned to receive lidocaine 5% patch (lidocaine group) or a placebo (placebo group) three days before thoracotomy. Postoperative analgesia was induced in all cases with intravenous morphine analgesia. The intergroup differences were assessed in order to evaluate whether the lidocaine patch 5% would have effects on pain intensity when at rest and after coughing (primary end‐point) on morphine consumption, on the recovery of respiratory function, and on peripheral painful pathways measured with N2 and P2 laser‐evoked potential (secondary end‐points). Results A total of 90 patients were randomized, of whom 45 were allocated to the lidocaine group and 45 to the placebo group. Lidocaine compared with the placebo group showed a significant reduction in pain intensity both at rest (P = 0.013) and after coughing (P = 0.015), and in total morphine consumption (P = 0.001); and also showed a better recovery of flow expiratory volume in one second (P = 0.025) and of forced vital capacity (P = 0.037). The placebo group compared with the lidocaine group presented a reduction in amplitude of N2 (P = 0.001) and P2 (P = 0.03), and an increase in the latency of N2 (P = 0.023) and P2 (P = 0.025) laser‐evoked potential. Conclusions The preventive skin analgesia with lidocaine patch 5% seems to be a valid adjunct to intravenous morphine analgesia for controlling post‐thoracotomy pain. However, our initial results should be corroborated/confirmed by larger studies.